Comparison of Facial Aesthetics Perception in Preclinical and Clinical Students of the Faculty of Dentistry, Lambung Mangkurat University - Alifa Rahma, Qantya Auliana; Dwi Kurniawan, Fajar Kusuma; Dewi, Renie Kumala; Sari, Galuh Dwinta; Nurrahman, Tri (Indonesian Dental Association, 2023)
Introduction: Facial aesthetics consist of facial symmetry, soft tissue profile, and vertical proportions of the face. Perception is subjective which means different things for each person. Aesthetic perception in dental students is very important because later in the future they will act as dentists and must understand about functional and aesthetics in the oral and facial cavities, and must be able to meet the needs and expectations of patients. Objective: To compare the perception of facial aesthetics with preclinical and clinical students of the Faculty of Dentistry, Lambung Mangkurat University. Methods: This study used analytical observational method with cross sectional approach. The sample size was calculated using an unpaired numerical comparative analytical formula, obtained by 128 respondents using the simple random sampling technique. Research respondents were given questionnaires totaling 15 photos, namely 5 photos of facial symmetry, 5 soft tissue profile photos, and 5 photos of vertical proportions of faces. The research questionnaire has been tested for validity and reliability. Results: The results of the Mann Whitney Test obtained an overall significance of 0.047 (p <0.05), facial symmetry 0.039 (p <0.05), soft tissue profile 0.385 (p >0.05), and vertical proportion of the face 0.612 (p >0.05). Conclusion: In three components of the assessment, there are differences in perception in facial symmetry, and there are no differences in perception in soft tissue profiles and facial vertical proportions. Overall, there are differences in the perception of facial aesthetics between preclinical students and clinical students of the Faculty of Dentistry, Lambung Mangkurat University.